Influence of environmental factors in the in vitro dehydration of hydrogel and silicone hydrogel contact lenses - Martín-Montañez, Vicente (2014)
Purpose: To analyze in vitro the influence of different environmental conditions on the dehydration pattern of seven currently marketed hydrogel (Hy) and silicone hydrogel (Si-Hy) contact lenses (CL). Methods: Three Hy and four Si-Hy CLs were evaluated. CLs were exposed to four different relative humidity (RH) conditions (5%, 30%, 50%, and 70%) and two air flow (AF) rates (0 and 2.75 m/seg) within an environmental chamber. Dehydration was assessed using the gravimetric method. Data were taken at baseline, 5, 10, 15, 20, 30, 45, 60, 90, and 120 minutes of exposure. Dehydration rate (DR), valid dehydration (VD) and stabilization time were calculated. Results: The interaction between RH, AF and the type of the CL material had a significant effect (p 0.03) on DR up to 60 minutes. The maximum differences in VD values among CL occurred around 15 minutes exposure varying from 25.16% to 42.75%. Stabilization time was quicker under the 5%RH with AF condition than under 70% RH without AF one for most CLs. Conclusions: Lower RH seems to increase CL dehydration being further accelerated with the AF presence. The dehydration pattern is material dependent, thus current marketed CLs behave differently under several controlled environmental conditions. Future in vivo studies should confirm these outcomes.